MICAN, a new fluorophore for vital and non-vital staining of human cells. (April 2018) - Nagy, Zsolt; Nagy, Miklós; Kiss, Alexandra; Rácz, Dávid; Barna, Beatrix; Könczöl, Péter; Bankó, Csaba; Bacsó, Zsolt; Kéki, Sándor; Banfalvi, Gaspar; Szemán-Nagy, Gábor
Abstract: Fluorescence time-lapse microscopy is in connection with the invasive properties of fluorochrome applied, and with the toxicity of the excitation energy and wavelength of the dye itself. Experiments with the newly synthesized fluorescent dye 1- N -methylamino-5-isocyanonaphthalene (MICAN) served to test its cytotoxicity on human HaCaT keratinocyte cell cultures. Experiments related to staining capability were performed with paraformaldehyde (PFA) fixed cells and observed with fluorescence microscope. It was assumed that the fluorophore 1-amino-5-isocyanonaphthalene (ICAN) and especially its N-methylamino derivative MICAN, containing condensed aromatic rings could serve as a nonselective fluorescent dye capable to stain cellular structures of fixed, living, damaged and dead cells. This notion was confirmed by the MICAN staining of cytoplasmic proteins primarily rough endoplasmic reticulum (RER), smooth endoplasmic reticulum (SEM) and less efficiently nuclear proteins suggesting the involvement of staining of subcellular structures involved in protein synthesis. MICAN was not only well tolerated by living cells but turned out to be a strong heterochromatin and RER staining agent. This led to the development of a MICAN staining protocol for native and living samples. Relative to other fluorescent dyes, MICAN is not only useful but also cost-effective. Toxicology tests were performed using 30, 10, 5, 0.5 μg/ml MICAN concentrations. Time-lapse videomicroscopy at near-infrared (NIR) illumination has been used for the examination of MICAN effect on cell division. It was found that MICAN as a vital stain had no significant harmful effect on HaCaT cells. MICAN turned out to be a non-toxic, highly quantum-efficient vital stain with minimal, or no photobleaching, and can be applied to co-stain with propidium-iodide due the strong spectral separation. Highlights: New family of fluorophores discovered First member of the family is MICAN. MICAN binds to cellular proteins similarly to rhodamin B. MICAN in non-toxic up to 10 μg/ml concentration Best staining conditions and emission are between 5 and 10 μg/ml.